Breast carcinoma and metastases in the interpectoral nodes: two observations - Toledo Correa, Nancy; Iraola, María L (Cirugía del Uruguay, 2021)
Accessory lymph vessels are of great importance in mammary cancer propagation. Especially those described by Rotter in 1899 ( transpectoral and retropectoral vessels). Interpectoral nodes may exist along the lymph trunks of that cell-containing space ( Rotter' s ganglia) . lt is not usual that the patient be examined with respect to these ganglia, therefore they may remain unnoticed by the pathologist. The authors twice found massive metastasis in these lymph nodes. . Consequently they consider it important .no conduct a sistematic examination of the mentioned ganglia, especially since there is a certain tendency among surgeons to preserve pectoral muscle in radical mastectomy.